IMPROVING LABOR RELATIONS IN THE DIGITAL ECONOMY - Shakarov Allayor Baratovich; Xudoyberdiyeva Maftuna Zayniddin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the challenges and opportunities in improving labor relations within the context of the digital economy. It discusses the impact of technological advancements, automation, and gig work on traditional labor structures. The article emphasizes the importance of fostering collaboration between employers, employees, and digital platform operators to create fair, transparent, and sustainable work environments. It highlights the need for updating labor laws and policies to accommodate the unique dynamics of digital work while ensuring workers’ rights are protected. The article also addresses the role of unions, collective bargaining, and the potential for new forms of worker representation in the digital economy.